A management information system for village health centers enhances the efficiency of healthcare delivery - Selli (PT. Lentera Ilmu Publisher, 2024)
The implementation of a Management Information System (MIS) in village health centers addresses the significant challenges posed by traditional paper-based record-keeping, limited resources, and inconsistent patient care. Village A, for example, benefits from a transition to integrated digital record-keeping, which ensures accurate data entry, reduces patient wait times, and enhances the overall efficiency of healthcare services. The MIS also improves supply chain management by tracking inventory in real-time, ensuring essential medical supplies are consistently available. Additionally, the system optimizes staff scheduling, mitigating the impact of staff shortages. In other villages, the MIS enhances the reliability of Electronic Health Records (EHR), merges paper and digital records for better accuracy, and introduces queue management systems to streamline patient flow. By addressing these challenges, the MIS significantly improves healthcare delivery, making it more efficient, responsive, and capable of meeting the specific needs of rural communities. This tailored approach not only enhances patient care but also strengthens the overall functionality of village health centers.